Personality theories of dispositional direction: comparative analysis of theoretical constructs and diagnostic means - Shevchuk, Olha (Psychological Prospects Journal, 2019)
The article represents the results of theoretical and empirical analysis of the most popular personality theories of dispositional direction – The Five-Factor Model (The Big Five) by Paul T. Costa, Jr. and Robert R. McCrae, L.R. Goldberg “transparent bipolar list”, H. J. Eysenck and R. B. Cattell trait theories. The domestic and foreign psychologists’ views on the prognostic potential of the constructs used to describe the psychological portrait of personality are analyzed. The main attempts of empirical verification of the diagnostic tools of dispositional direction theories are stated. The main aim of the described research procedure was to establish statistically significant correlations between P. T. Costa and R. R. McCrae’s Five-Factor Model, L. R. Goldberg’s related theory, H. J. Eysenck and R. B. Cattell trait theories. 589 statistically significant correlations were identified and analyzed using mathematical statistics methods. Both positive and negative correlations between methods parameters were taken into account. The interpretation results allow describing the semantic space of each construct with the help of the correlated scales’ names and therefore can be drawn conclusions of causally consequential character. It was grounded, that correlation analysis testifies about the high cross construct validity of translated by us into Ukrainian questionnaires, since all cognominal scales correlate with each other. Four super factors, with the help of which a personality can be described, were singled out as the result of empirical research: emotional stability–neuroticism, introversion-–extraversion, antagonism–benevolence, psychoticism –- power of superego. The approbation of the translated into Ukrainian dispositional direction questionnaires was made.